Second-order duality for nondifferentiable multiobjective programming involving (Φ,ρ)-univexity - Thakur, Ganesh Kumar; Priya, Bandana (Kathmandu University Journal of Science Engineering and Technology, 2011)
The concepts of (Φ, ρ)-invexity have been given by Carsiti,Ferrara and Stefanescu[32]. We consider a second-order dual model associated to a multiobjective programming problem involving support functions and a weak duality result is established under appropriate second-order (Φ, ρ)-univexity conditions.